FRI0609 Ultrasonography is a Useful Modality with Ease Access Reflecting Local Molecular Pathophysiology of Inflammatory Joint in Rheumatoid Arthritis. (9th June 2015) - Kondo, Y.; Suzuki, K.; Inoue, Y.; Takeshita, M.; Morita, R.; Kasai, Y.; Miyazaki, T.; Niki, Y.; Hanaoka, H.; Kaneko, Y.; Yasuoka, H.; Yamaoka, K.; et al.
Abstract : Background: Number of cytokines including tumor necrosis factor (TNF)-α, interleukin (IL)-6 and IL-1 play important roles in the pathogenesis of rheumatoid arthritis (RA). Biologics have become an effective therapeutic agent, although definition of "effect" largely relies on subjective evaluation by the physician and patient. Ultrasonography (US) is a useful modality that can directly visualize joint inflammation such as synovial thickening and vascularization and has been reported as a useful tool for objective evaluation of RA activity. However, association with pathophysiology of RA is poorly unknown and requires further evaluation. Objectives: To clarify the association of joint US findings and cytokine levels in synovial fluid (SF). Methods: This was a cross-sectional study. Thirty-six RA patients and 24 osteoarthritis (OA) patients were enrolled. SF aspiration was performed in 28 RA patients and the followings were measured; IL-6, IL-8, TNF-α, IL-1β, IL-10, IL-17A, IL-12/23p40, Fractalkine, VEGF, MMP-3, Granzyme A and Granzyme B. The knee joint US scans were assessed at the suprapatellar pouch, lateral and medial artcular recesses. Gray scale ultrasound (GSUS) and power Doppler ultrasound (PDUS) were analyzed by 2 experienced rheumatologists blinded to clinical information. US findings were graded on a semi-quantitative scale from 0 to 3 and mean GSUS and PDUS scores were calculated in three areas of the knee joint aforementioned. Results: Median age, disease duration and DAS28-ESR were 63 years, 5 years and 5.33 respectively. Mean GSUS and PDUS were 2.37 and 1.78. The intraclass correlation coefficient values for inter-observer agreement of GSUS and PDUS were good and notably better in PDUS (GSUS; 0.716, PDUS; 0.909). IL-6, IL-8, TNF-α, IL-1β, IL-10, IL-17A, IL-12/23p40, MMP-3, Granzyme A and B in RASF were significantly higher compared to OASF. US findings especially PDUS of RA knee joint well correlated with SF IL-6, IL-8, IL-1β and IL-10. (GSUS; range of ρ=0.40 to 0.44, p<0.05, PDUS range of ρ=0.49 to 0.59, p<0.01, summarized in Table.1 and Figure 1 .) Additionally PDUS correlated with VEGF involved in vasculogenesis (ρ=0.40, p=0.03), fractalkine expressed in RA synovial endothelial cells (ρ=0.42, p=0.03) and SF total cell count (ρ=0.64, p<0.01) while GSUS associated with SF MMP-3. (ρ=0.55, p<0.01) Conclusions: US findings especially PDUS of RA affected joint well correlated with RA SF cytokines and cell number. Our results suggest that US is a useful modality with ease access reflecting local molecular pathophysiology of inflammatory joint in RA. References: Naredo E et al. Arthritis Rheum 2008; 58: 2248–56 Schmidt WA et al. Ann Rheum Dis 2004; 63: 988–94. Nicola J et al. PLoS One. 2010 Sep 1;5(9). Disclosure of Interest: Y. Kondo: None declared, K. Suzuki Grant/research support from: Eisai Co.Ltd. and Bristol-Myers Squibb Company, Y. Inoue: None declared, M. Takeshita: None declared, R. Morita: None declared, Y. Kasai Employee of: Takeda Pharmaceutical Company Limited, T. Miyazaki Employee of: Takeda Pharmaceutical Company Limited, Y. Niki: None declared, H. Hanaoka Consultant for: Astrazeneca, Y. Kaneko Consultant for: Abbvie, Paid instructor for: Eisai Pharmaceutical, Chugai Pharmaceutical, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Speakers bureau: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Janssen, UCB, H. Yasuoka Consultant for: Abbvie, K. Yamaoka: None declared, A. Yoshimura Consultant for: Pfizer, Speakers bureau: Pfizer, Chugai Pharma, Mitsubishi-Tanabe Pharma, Takeda Industrial Pharma, GlaxoSmithKline, Nippon Shinyaku, Eli Lilly, Janssen Pharma, Eisai Pharma, Astellas Pharma and Actelion Pharmaceuticals, T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., and Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd., Bristol–Myers K.K., Nipponkayaku Co.Ltd., Paid instructor for: Mitsubishi Tanabe Pharma Co., Eisai Co., Ltd., Abbivie GK, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, and Diaichi Sankyo Co., Ltd., Celtrion, Nipponkayaku Co.Ltd